1994
DOI: 10.1002/anie.199423321
|View full text |Cite
|
Sign up to set email alerts
|

Phase Transitions in Self‐Assembled Monolayers Detected by Electrochemistry

Abstract: COMMUNICATIONSN M R evidence for a persistent phosphirenyl cation in a compound formulated as (PhiBuC,P)+[B(OSO,CF,)J .f2 '] In 4, the slightly shorter C -C bond length (1.33(3)A) and the elongated P-C bonds (1.78(2)A and 1.82(2)A) would suggest incomplete delocalization when compared with the theoretical models of the free ligand. although the effect of a bound transition metal fragment on the latter is not clear. The Ni-PI bond (2.207(5)A) in 4 lies close to the average Ni-P bond length found by H,tBu2)]. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
68
0

Year Published

1998
1998
2009
2009

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 55 publications
(78 citation statements)
references
References 58 publications
10
68
0
Order By: Relevance
“…The chain melting of n-C n H 2n + 1 thiol-coated gold nanoparticles occurs at the following temperatures for the indicated chain length: 3°C (n = 12), 22°C (n = 14), 41°C (n = 16), 51°C (n = 18), and 64°C (n = 20) [25]. These 'melting' transition temperatures are quite comparable to those found for gold SAMs, for which the temperatures are found to be: 39°C (n = 16), 53°C (n = 18), and 63°C (n = 20), measured electrochemically [26]. Gold nanoparticles coated with alkylthiol chains having 12, 10, and 8 carbons display broad melt transitions at temperatures less than 0°C, indicating they are melted at room temperature, as evidenced by the viscous nature of these materials.…”
Section: Resultssupporting
confidence: 65%
“…The chain melting of n-C n H 2n + 1 thiol-coated gold nanoparticles occurs at the following temperatures for the indicated chain length: 3°C (n = 12), 22°C (n = 14), 41°C (n = 16), 51°C (n = 18), and 64°C (n = 20) [25]. These 'melting' transition temperatures are quite comparable to those found for gold SAMs, for which the temperatures are found to be: 39°C (n = 16), 53°C (n = 18), and 63°C (n = 20), measured electrochemically [26]. Gold nanoparticles coated with alkylthiol chains having 12, 10, and 8 carbons display broad melt transitions at temperatures less than 0°C, indicating they are melted at room temperature, as evidenced by the viscous nature of these materials.…”
Section: Resultssupporting
confidence: 65%
“…We found the same behaviour as for the double layer current mentioned above: the redox waves' current rose at high temperatures and for short chain lengths. Note that the temperature behaviour can be more complex [68]. Experiments with Ru(NH3)6/2+ normally showed a much higher current; however, the same dependence on the thiolate chain length is found (Fig.…”
Section: Thiolate Layers and The Electrodeposition Of Metalsmentioning
confidence: 76%
“…Using in situ vibrational spectroscopy they confirmed that this behaviour is due to phase transitions of the monolayer. The electrochemical studies carried out by Badia et al confirm the order-disorder transitions in SAMs [142]. They too found a chain length dependence of melting temperature; the values vary between 313 and 338 K.…”
Section: Electrochemical and Electrical Propertiesmentioning
confidence: 82%